PERAN PENGAWAS PENDIDIKAN DALAM MENDORONG INSPIRASI DAN PENINGKATAN KINERJA GURU DI KABUPATEN GORONTALO - Yahya Yunus Anuli (Journal of Islamic Education Management Research, 2025)
This study aims to analyze the strategic role of Islamic Education (PAI) supervisors in enhancing teacher inspiration and performance in Gorontalo Regency, focusing on the districts of Tabongo, Batudaa, and Tilango. The research adopts a literature review approach by examining various relevant academic sources and applying thematic analysis. The results reveal that PAI supervisors have evolved beyond administrative evaluators into inspirators, facilitators, and professional partners for teachers. The implementation of clinical supervision, coaching-based supervision, and collaborative supervision models has proven effective in improving teachers’ pedagogical competence, intrinsic motivation, and instructional creativity. In addition, the integration of Islamic values and local wisdom such as huyula (mutual cooperation) plays a significant role in establishing contextual and sustainable supervisory practices. Key supporting factors include supervisors’ competence, interpersonal communication skills, and institutional support, while major challenges involve limited supervisory resources and negative teacher perceptions of supervision. Therefore, PAI supervisors play a crucial role in improving educational quality through inspirational and collaborative approaches.